Molecular Genetic Strategies in the Study of Corticohippocampal Circuits - Angelakos, Christopher C. (Cold Spring Harb Perspect Biol, 2015)
The first reproductively viable genetically modified mice were created in 1982 by Richard Palmiter and Ralph Brinster (Palmiter RD, Brinster RL, Hammer RE, Trumbauer ME, Rosenfeld MG, Birnberg NC, Evans RM. 1982. Dramatic growth of mice that develop from eggs microinjected with metallothionein-growth hormone fusion genes. Nature 300: 611–615). In the subsequent 30 plus years, numerous ground-breaking technical advancements in genetic manipulation have paved the way for improved spatially and temporally targeted research. Molecular genetic studies have been especially useful for probing the molecules and circuits underlying how organisms learn and remember—one of the most interesting and intensively investigated questions in neuroscience research. Here, we discuss selected genetic tools, focusing on corticohippocampal circuits and their implications for understanding learning and memory.